PAI Teacher’s Strategy in Improving Student Achievement at MAN PK MAN 4 Jombang - Dina Maulidiyah Ningrum; Try Heni Aprilia; Mahdee Maduarawee (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This study is motivated by the fact that educational strategies in Indonesia are generally still mass-oriented, treating all students’ potential as the same, despite individual differences in learning styles, skills, intelligence, interests, and talents. MAN PK MAN 4 Jombang, as a leading Islamic educational institution, has demonstrated the ability to produce high-quality graduates who achieve academically and non-academically, many of whom continue their studies at prestigious universities domestically and abroad. This research aims to describe the strategies used by Islamic Education teachers to improve students' achievements, focusing on learning objectives, approaches, methods, and success criteria. Using a qualitative case study design, data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing, with validity ensured by observation persistence and triangulation. The findings reveal: (1) The learning objective is to enable students to master subject matter and become intellectual scholars with strong knowledge and application skills. Teachers determine objectives based on students’ competencies and integrate intra-curricular, co-curricular, and extracurricular activities. (2) The approaches vary according to material and student characteristics, including role modeling, inquiry, constructivism, behaviorism, technology-based, scientific, and inclusive methods. (3) Teaching methods combine lectures, discussions, demonstrations, collaboration, storytelling, and reward-giving, supported by techniques like group work, projects, and presentations. The teaching process consists of an introduction, core activities, and a closing. (4) Academic achievement is assessed through report card scores, while non-academic evaluation is informal, considering student manners, competition achievements, personal development, and learning behavior.